Dental Implant Failure Risk in Patients with Bruxism—A Systematic Review and Meta-Analysis of the Literature - Josephine A. Ionfrida; Hanna L. Stiller; Peer W. Kämmerer; Christian Walter (Dentistry Journal)
Background/Objectives: Recent research has indicated that placing dental implants in patients diagnosed with bruxism has led to higher rates of implant failure. This study aimed to provide more accurate knowledge about the relationship between bruxism and implant loss in patients (number, age, gender) with different numbers of implants and prosthetic restorations, considering the follow-up time, compared to non-bruxers. Methods: A systematic search was conducted in PubMed and Cochrane Library using the keyword combination “dental implant”, “bruxism”, and “implant failure”. This search had no language or time restrictions. Results: The review included 15 papers, which were divided into four groups. The first group focused on studies regarding implant loss regardless of the superstructure. In the second group, research on implant-supported removable prostheses was examined. The third group consisted of a single study specifically addressing implant-supported single crowns. Lastly, the fourth group comprised two studies investigating implant-supported single crowns and fixed partial dentures. Only three out of the fifteen studies failed to find a correlation between bruxism and implant failure. The meta-analysis shows a significant pooled effect across the included studies, with an odds ratio of 4.68. Conclusions: Bruxism is a probable risk factor for mechanical issues in implant-supported prostheses and implant-supported crowns. Additionally, elevated failure rates have been documented in patients with bruxism.